Comparison Between 0.5% and 0.75% Hyperbaric Bupivacaine Given Intrathecally in Elective Caesarian Section - Zahid, Anas; Hussain, Abid; Matloob, Rimsha; Fatima, Mehrab; Rehman, Sami Ur; Qureshi, Muhammad Mushtaq Ahmed (Biological and Clinical Sciences Research Journal, 2026)
Spinal anesthesia is the preferred anesthetic technique for elective caesarean section because of its rapid onset, reliability, and favorable maternal and fetal safety profile. However, hypotension and other hemodynamic disturbances remain common concerns, and the concentration of hyperbaric bupivacaine may influence these effects. Objective: To compare maternal hemodynamic changes associated with 12 mg of 0.5% versus 12 mg of 0.75% hyperbaric bupivacaine for spinal anesthesia in elective caesarean section. Methods: This randomized controlled trial was conducted at Abbas Institute of Medical Sciences, Muzaffarabad, from April 2024 to September 2024. A total of 100 women aged 20 to 40 years with American Society of Anesthesiologists physical status I or II undergoing elective caesarean section were randomly allocated into two equal groups. Group A received 12 mg of 0.5% hyperbaric bupivacaine, while Group B received 12 mg of 0.75% hyperbaric bupivacaine. Hemodynamic parameters, including systolic blood pressure and heart rate, were recorded at predefined intervals after spinal anesthesia. Adverse effects, sensory block level, vasopressor requirement, and patient satisfaction were also assessed. Results: Baseline demographic characteristics were comparable between the groups. Both regimens produced adequate spinal anesthesia, with T4 sensory block achieved in 86% of patients in Group A and 82% in Group B. Although between-group differences in systolic blood pressure and heart rate at measured time points were not statistically significant, Group A showed a trend toward greater hemodynamic stability. Nausea and vomiting occurred less frequently in Group A than in Group B (18% vs 38%). Bradycardia was observed only in Group B (4%), and hypotension was less frequent in Group A (6% vs 14%). A significantly greater proportion of patients in Group A required no rescue vasopressor compared with Group B (94% vs 80%; p = 0.038). Patient satisfaction was also higher in Group A (78% vs 66%). Conclusion: Both concentrations of hyperbaric bupivacaine provided effective spinal anesthesia for elective caesarean section. Although the differences in serial hemodynamic parameters were not statistically significant, 0.5% hyperbaric bupivacaine was associated with fewer adverse effects, lower vasopressor requirement, and better patient satisfaction, suggesting a more favorable clinical profile.